Some common assets between the beliefs of the old Iraqi and beliefs of African peoples Old Town - هاشم معضد, علي (Al-Adab Journal, 2018)
African people belongs to the four ancient ethnic groups representing the indigenous people of the continent, in addition to Al-Hamian , and the Semitic Negro people , and Arab-Semitic elements, and found in the continent , the oldest civilizations that have influenced and affected in many civilizations entire Arab region.The religions and traditional beliefs in African belong mostly to the multiple gods class religions. And the Incredible people in these religions are different spirits (including the spirits of the place and ancestral spirits, and the spirits of the phenomena of nature ... etc) but they are not gods, and thus multiple religions and gods are the first African societies ([i]), which is so common with the first civilized societies formed in the Arab region, just like the civilization of Mesopotamia and Nile valley , where characterized the religion with the principle of polytheism and similarity the people with kings and goddess ([ ii]), it is known to be a citizen in the civilizations of West Africa (West and East Sudan, the area of ​​the Gulf of Benin) and between the lakes (Uganda) the religions incarnation of God in a number of people. Overall, religions, traditional African, whether the multiple gods, or those which embodied God in one person , and not well-suited for the system dictates the spiritual teachings of members of the same society in Africa, but the religious and social practices are characteristic dominant on the behavior of societies in general, both in civilizations Arab societies and in Africa societies .